2019
DOI: 10.1002/adma.201900568
|View full text |Cite
|
Sign up to set email alerts
|

High Phase Purity of Large‐Sized 1T′‐MoS2 Monolayers with 2D Superconductivity

Abstract: The development of transition metal dichalcogenides has greatly accelerated research in the 2D realm, especially for layered MoS2. Crucially, the metallic MoS2 monolayer is an ideal platform in which novel topological electronic states can emerge and also exhibits excellent energy conversion and storage properties. However, as its intrinsic metallic phase, little is known about the nature of 2D 1T′‐MoS2, probably because of limited phase uniformity (<80%) and lateral size (usually <1 µm) in produced mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 32 publications
3
96
0
Order By: Relevance
“…It is also reported that intercalation compounds containing other alkali metals, such as sodium and rubidium, can be used as precursors in the synthesis of 1T 00 0 MoS 2 single crystals. 56 Bulk crystals of the 1T 0 MoSe 2 with lateral size B100 mm have been demonstrated through a similar deintercalation (with I 2 solution) of a precursor obtained through a chemical reaction between alkali metal containing molybdenum precursors, such as potassium or sodium molybdate, and elemental selenium annealed in an inert atmosphere in an ampoule 69 or in an open system in a reducing H 2 /Ar atmosphere 68 (Fig. 5d).…”
Section: Electron Doping By Contacting With An Electron Reservoirmentioning
confidence: 77%
See 3 more Smart Citations
“…It is also reported that intercalation compounds containing other alkali metals, such as sodium and rubidium, can be used as precursors in the synthesis of 1T 00 0 MoS 2 single crystals. 56 Bulk crystals of the 1T 0 MoSe 2 with lateral size B100 mm have been demonstrated through a similar deintercalation (with I 2 solution) of a precursor obtained through a chemical reaction between alkali metal containing molybdenum precursors, such as potassium or sodium molybdate, and elemental selenium annealed in an inert atmosphere in an ampoule 69 or in an open system in a reducing H 2 /Ar atmosphere 68 (Fig. 5d).…”
Section: Electron Doping By Contacting With An Electron Reservoirmentioning
confidence: 77%
“…66,67 Due to a large energy difference between the 2H and 1T 0 phases, the metastable group VI diselenides and disulphides are challenging to obtain in a pure form and the reports on their successful synthesis are limited. 21,[68][69][70][71] The crystal structure of the monoclinic 1T 0 phase of group VI diselenides and disulphides is still debated with the possible space groups being either P2 1 /m or C2/m; the latter has only been reported recently and is referred to as the 2M phase, where M stands for the monoclinic lattice system. 72 Unlike the semiconducting 2H counterparts, the corresponding 1T 0 and Td phases of group VI TMDs are semimetallic.…”
Section: Structural Polymorphs Of Group VI Tmdsmentioning
confidence: 99%
See 2 more Smart Citations
“…I norganic two-dimensional (2D) materials, such as graphene, graphene oxide (GO), transition metal dichalcogenides (TMDs), hexagonal boron nitride (h-BN) and black phosphorus (BP), have received unprecedented attention in recent years due to their unusual chemical and physical properties [1][2][3][4][5][6][7][8] . Electronic band gaps are determinative in the electronic transportation and optical properties of these 2D materials [9][10][11] .…”
mentioning
confidence: 99%